Integrating Facial Emotion Recognition, Speech to Text Transcription, and Natural Language Processing for Customer Satisfaction Analysis from Video Reviews - Deshpande, Sudhindra B.; Michael, Goh Kah Ong; Deshpande, Uttam U.; Mathad, K. S.; Karekar, N. V.; Tangod, Kiran K. (Engineering, Technology & Applied Science Research, 2026)
Customer satisfaction is a decisive factor in the success of products and services provided, yet conventional text-based reviews often fail to capture the full spectrum of user emotions needed to assess satisfaction. On the other hand, video product or service reviews offer a more informative medium for evaluating customer satisfaction. To leverage this, the present study proposes a multimodal machine learning framework for video-based customer feedback analysis, integrating facial emotion recognition, speech-to-text transcription, and Natural Language Processing (NLP). A dataset of 1,000 video reviews was processed through a multistage pipeline that involved frame extraction, face detection, emotion classification, audio transcription, sentiment analysis, and late fusion of modalities. Experimental results highlight the limitations of unimodal models: visual-only sentiment prediction achieved 62.3% accuracy (precision = 0.61, recall = 0.63, F1-score = 0.62, Area Under Curve (AUC) = 0.65), while audio-only sentiment prediction reached 59.5% accuracy (precision = 0.58, recall = 0.59, F1-score = 0.59, AUC = 0.61). The text-based model provided a stronger baseline at 72.1% accuracy (precision = 0.70, recall = 0.72, F1-score = 0.71, AUC = 0.75). In contrast, the multimodal fusion framework substantially outperformed unimodal approaches, achieving 79.9% accuracy, precision = 0.80, recall = 0.81, F1-score = 0.80, and the highest AUC of 0.86. Additionally, aspect-level analysis revealed that camera quality (+0.16) was the most positively perceived feature, while app performance (-0.33) and delivery (-0.09) emerged as primary concerns. Temporal analysis showed satisfaction scores fluctuating between 52.1 and 63.4 (0-100 scale) over 20 weeks, underscoring the value of continuous monitoring. These findings demonstrate that multimodal video feedback analysis yields more comprehensive, reliable, and fair performance than single-channel methods.